Analysis of variability, heritability and trait association in four F2 populations of Gossypium hirsutum L. - K. Yaksha1, S. Rajeswari2, N. Premalatha2 and N. Manikanda Boopathi3 (Electronic Journal of Plant Breeding)
Cotton is a prime crop of industrial importance. The assessment of variability provides scope for planning the breeding programmes. This study was conducted at Tamil Nadu Agricultural University, Coimbatore in F2 generation for the crosses viz., CO 17 x KC 2, TVH 002 x KC 3, TVH002 x RAHC 1039 and TCH 1894 x NDLH 32 to estimate the variability, trait heritability and correlation among traits. In this experiment, high PCV paired with high GCV was noted for number of monopodia per plant as well as boll weight in all the four crosses. High heritability along with high genetic advance as per cent of mean were noted among all the crosses for seed index, boll weight, plant height and lint index. The plant yield of a single plant in all the crosses was noted to be significant and positively correlated with lint index, number of bolls per plant, internode length, boll weight and plant height.